Application of Yoga Gymnasticson Clients with Hypertension as an Effort to Lower Blood Pressure: A Case Study - S, Saprianto; Putri, Meti Eka (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: hypertension is an increase in abnormal arterial blood pressure, namely blood pressure more than 140/90mmHg. Hypertension, a silent killer or "silent killer". That is a familiar nickname for hypertension or high blood pressure. Every year there is an increase in hypertension sufferers from year to year, this is due in large part to the lack of knowledge of how to treat and causes of hypertension, Broadly speaking, therapy or management of hypertension can be done in two ways, namely pharmacological management (with drugs) and non-pharmacological (without drugs), one of which is the application of yoga exercises to lower blood pressure. Objectives: To determine the effectiveness of the application of yoga exercises to clients with hypertension to reduce blood pressure. Methods: This research design uses a case study method that implements the application of yoga exercises to clients with hypertension to reduce blood pressure. Results: Researchers found that there was an effect of the application of yoga exercises on hypertensive clients on lowering blood pressure. Conclusion: After applying Yoga Gymnastics to patients with hypertension in the work area of ​​the Tanjung Agung Health Center, the researchers concluded that the Effective Yoga Exercise helps reduce blood pressure. Suggestion: Further researchers are advised to increase the number of respondents so that they can reduce blood pressure more from this study.